2020
DOI: 10.1016/j.hrthm.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic (hydroxy)chloroquine in COVID-19: Potential relevance for cardiac arrhythmia risk

Abstract: of the Heart (ERN GUARDHEART; https://guardheart.ern-net.eu), and ‡ European Cardiac Arrhythmia Genetics Focus Group (ECGen) of the European Heart Rhythm Association (EHRA).(Hydroxy)chloroquine ((H)CQ) is being investigated as a treatment for COVID-19, but studies have so far demonstrated either no or a small benefit. However, these studies have been mostly performed in patients admitted to the hospital and hence likely already (severely) affected. Another suggested approach uses prophylactic (H)CQ treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Acidic endolysosomes are also important for autophagy, which is important for initiating innate immune responses and the degradation of viruses ( Dalpke and Helm, 2012 ; Choi et al, 2018a ). Accordingly, de-acidification of endolysosomes might hamper autophagy-mediated antiviral responses ( Kužnik et al, 2011 ) by deactivating RNA sensors ( Belizaire and Unanue, 2009 ; Kužnik et al, 2011 ; Kazi et al, 2013 ; Hussman, 2020 ; Offerhaus et al, 2020 ; Schrezenmeier and Dörner, 2020 ). Therefore, improving innate immune responses using synthetic RNAs, oligonucleotides, or small agonists of TLRs as well as type-I interferon treatment might improve clinical responses to CQ and HCQ ( Dalpke and Helm, 2012 ; Freund et al, 2019 ; Hussman, 2020 ; Lee and Shin, 2020 ).…”
Section: Endolysosome-based Therapeutic Strategies To Inhibit Severe mentioning
confidence: 99%
“…Acidic endolysosomes are also important for autophagy, which is important for initiating innate immune responses and the degradation of viruses ( Dalpke and Helm, 2012 ; Choi et al, 2018a ). Accordingly, de-acidification of endolysosomes might hamper autophagy-mediated antiviral responses ( Kužnik et al, 2011 ) by deactivating RNA sensors ( Belizaire and Unanue, 2009 ; Kužnik et al, 2011 ; Kazi et al, 2013 ; Hussman, 2020 ; Offerhaus et al, 2020 ; Schrezenmeier and Dörner, 2020 ). Therefore, improving innate immune responses using synthetic RNAs, oligonucleotides, or small agonists of TLRs as well as type-I interferon treatment might improve clinical responses to CQ and HCQ ( Dalpke and Helm, 2012 ; Freund et al, 2019 ; Hussman, 2020 ; Lee and Shin, 2020 ).…”
Section: Endolysosome-based Therapeutic Strategies To Inhibit Severe mentioning
confidence: 99%
“…In fact, a recent clinical trial conducted by Self et al concluded that HCQ did not improve clinical status at day 14 of COVID-19 patients; thus, its use was not supported [ 103 ]. However, several reasons may be associated with this trend, such as different in vitro and in vivo results and conduction of recent studies in critically ill patients and, hence, the administration of HCQ in the later stage of the disease; while, most of its mechanisms of inhibition of viral replication are effective during early disease [ 104 ]. Therefore, the data available for HCQ show both promising early therapeutic benefits and existing concerns.…”
Section: Cardiovascular Involvement In Covid-19 Patientsmentioning
confidence: 99%
“…HCQ is not only known to mildly block the human ether-à-go-go related gene (hERG) aka KCNH2 that codes for delayed rectifier potassium channel, but also the inward-rectifier potassium channel [ 111 ]. This interferes with ventricular repolarization, resulting in a continuous action potential which causes significant prolongation of QT interval [ 104 , 112 ]. Thus, HCQ is proarrhythmic, increasing the risk of torsades de pointes and other ventricular arrhythmias [ 66 ].…”
Section: Cardiovascular Involvement In Covid-19 Patientsmentioning
confidence: 99%
“…While CQ and HCQ also have similar toxicity profiles and are equipotent, chloroquine is much more toxic (2-fold) [ 16 ]. Although short-term administration of either drug is generally well-tolerated, except in patients predisposed to arrhythmia, chronic dosing and high-dose regimens can cause severe side effects such as irreversible retinal toxicity [ 17 , 18 , 19 ]. CQ and HCQ have similar pharmacokinetic (PK) properties, including high volume of distribution and prolonged plasma half-lives between 40 and 50 days, which requires weeks of dosing to achieve steady-state therapeutic concentrations [ 20 ].…”
Section: Introductionmentioning
confidence: 99%